IT-based innovation and new product development performance in Yemen: the moderating role of intellectual property - A. Jandab, Abdulwahab; Ali, Noor Azman; Abdulsamad, Akram; Mohammed Al-Sharif, Abdulrahman (Forecast Publisher, 2019)
Purpose: This study seeks to investigate the relationship between IT-based innovation (ITI) and new product development performance (NPDP) in the context of Diffusion of Innovation (DOI) theory; as well as it aims to examine the moderation effect of intellectual property (IP) on this relationship. Design/ Method/ Approach: Quantitative data were acquired for firms that are presently members of the federation of Yemen chambers of commerce and industry. Survey outcomes of 700 Yemeni food processing SMEs provide considerable results for this study. SmartPLS-3 was used with the purpose to analyze returned responses, validate the study model, and test the hypotheses. Findings: Results indicate that there is a positive direct relationship between ITI and NPDP, as well as, the results show an insignificant moderating effect of IP in the relationship between ITI and NPDP. Originality/Value: This study contributes to the body of knowledge on the role of IT-based innovation in the performance of new product development. It further examined the moderating effects of IP on the relationship between IT-based innovation and new product development performance. The study was conducted in Yemen, a non-western and developing context. Practical implications: The practical implications of the findings to top management and practitioners are presented. The benefits of this study can be enjoyed by SMEs in the Yemeni food processing sector and the nation at large.